Application of multiple binding sites for LAMP primers across P. falciparum genome improves detection of the parasite from whole blood samples - Mgawe, Cavin; Shilluli, Clement; Nyanjom, Steven; Odari, Eddy; Linnes, Jacqueline C.; Kanoi, Bernard N.; Gitaka, Jesse; Ochola, Lucy (Frontiers in Malaria, 2023)
analysis with the nested PCR showed a perfect agreement between the two techniques. (K = 0.99 for whole blood, and 0.66 for saliva).Our study presents a method for detecting P. falciparum using LAMP, which results in increased sensitivity, shorter assay times, and a simpler workflow than nucleic acid tests relying on conventional DNA extraction and additional equipment for result interpretation. These findings hold great promise for improved malaria diagnosis, especially in settings where low-density parasitaemia is prevalent and rapid and accurate malaria detection is crucial.